Public and private universities: Timely scenarios for scientific production in health sciences - Gómez-Gonzales, Walter (2020)
University education in Peru is currently characterized by massification, allowing young people from different socioeconomic strata access to public and private higher education institutions. Consequently, more and more people, after several years of study, manage to attain a professional degree or an academic degree.